Preparation of anionic-exchange membranes composites for acid recovery from acidic wastewater - P. Pattiyatanee; W. Chonkaew; S.P Thanasupsin (International Association of Lowland Technology, 2018)
This study aimed to prepare the anion exchange membrane (AEM) from brominated poly (2, 6-dimethyl-1, 4-phenylene oxide)/polypyrrole (BPPO/Ppy) composites, and to study the effects of pyrrole (Py) concentrations and amination reaction on conductivity and transport properties of the membranes. The 8 wt% PPO was reacted with 20 wt% Br2 in chlorobenzene solutions at a control temperature of 131℃. The obtained product was characterized by FTIR and H-NMR to confirm the benzyl bromination on PPO. BPPO membranes were prepared by solution casting method (thickness 0.45 - 0.5 mm). The BPPO/Ppy composites were prepared by soaking the BPPO membrane in Py solution (vary from 0.3 – 0.5 mol dm-3 for 24 hr. The ion exchange capacity (IEC), water uptake (WR) and conductivity of the membranes were investigated. The effects of amination reaction with 0.5 mol.dm-3 trimethylamine (TMA) were also studied. The results showed that ion exchange capacity (IEC), conductivities and water uptake and acid permeability of composite membranes were enhanced by amination reaction. However, the BPPO/Ppy composite membrane without TMA amination was found to provide the better acid diffusion coefficient than that with TMA. Further investigations should focus on fine tuning the conditions to obtain high hydrophilicity, water uptake and ion selectivity rejection.